"D.C. is mambo sauce": Black cultural production in a gentrifying city. Issue 3 (November 2020) - Reese, Ashanté M.
Centering mambo sauce as both a cultural staple and a metaphor for struggles over ownership in Washington, D.C., this article explores mambo sauce's role in constructing a D.C. identity. Drawing on data from ethnographic interviews and newspaper headlines, I argue that, against the background of intense and consistent gentrification that has left the city's population younger, whiter, and wealthier, mambo sauce becomes a lens through which to examine larger tensions related to race, class, and power. Specifically, I examine mambo sauce as a form of Black cultural production to explore the dialectical relationship between how mambo travels well beyond the carryout restaurants in Black working-class neighborhoods and the displacement of Black residents in the gentrifying city.